Proses Gentrifikasi Di Perkotaan Yogyakarta - Putri, Winda Ayu (Jurnal Perencanaan dan Pengembangan Kebijakan, 2024)
Gentrification is a process of socio-economic transformation in which areas previously inhabited by low-income or low-middle-income residents are gradually inhabited by higher-income residents. This research combines a case study methodology with a qualitative approach to examine the dynamics of social, economic, and physical changes in several areas affected by gentrification in Yogyakarta, such as Prawirotaman, Kotabaru, and Sosrowijayan. Through in-depth interviews, data were gathered with local residents, entrepreneurs, and government officials, as well as analysis of urban planning documents and statistical data. The results show that gentrification in Yogyakarta is triggered by number of causes, including an increase in the tourism sector, investment in property, and government policies that encourage slum revitalization. The impacts of gentrification include increased property prices, displacement of indigenous residents, changes in cultural character, and social conflicts between newcomers and longtime residents.